The differences between teams in men`s and women`s medallists and non-medallists at the 1996-2016 Olympic Games artistic gymnastics tournament - Atikovic, A.; Kalinski, S. D.; Petkovic, E.; Cuk, I. (Central European Journal of Sport Sciences and Medicine, 2017)
The aim of this study is to determine the differences between the medallists and non-medallists in male and female artistic gymnastics at the Olympic Games from 1996 to 2016. Basic procedures: Data concerning the athletes were obtained from the "Official documents of the International Olympic Committee" which include the athlete`s date of birth and date of competing. The total number of analysed OG participants in men`s artistic gymnastics amounted to n = 419 and the women`s artistic gymnastics was n = 417. Main findings: With men the t test for small independent samples has determined statistically significant differences between medallists and other competitors in 2000 and 2012. Among women no significant statistical differences have been found in all the mentioned variables. Conclusions: The differences between male medallists and non-medallists are manifested through the age of the competitors: 2.57 years in 2000 and 3.57 years in 2012. Compared to other OG a higher level of homogeneity and smaller age difference is noticeable. In difference to men, women had no similar differences within a period of 20 years. In artistic gymnastics in the last couple of years there is a recurring trend of a late specialisation because with each new scoring Code of Points the conditions demanded from the competitors become harder.